Personnel protection and safety equipment for the oil and gas industries - Bahadori, Alireza (Gulf Professional Publishing is an imprint of Elsevier, 2015)
Oil and gas companies are repeatedly cited by regulatory organizations for poor training and maintenance on providing personal protective equipment to their refinery workers. Managers of refinery and petrochemical plants are responsible for instructing their workers with the types of equipment available, how to properly wear the equipment, how to properly care and maintain the equipment, and, most importantly, it's their responsibility to enforce these regulations and safety requirements. While there are many reference materials on the subject, most are too broad to apply directly to the uniq.
Keywords: Breathing apparatus.; Protective clothing.; Gas industry -- Safety measures.; Petroleum industry and trade -- Safety measures.; elektronické knihy; electronic books